2020
DOI: 10.1002/slct.202002256
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Carbonylative Synthesis of Aromatic Esters and Formation of Quinazoline‐2,4(1H,3H)‐diones by Chemical Fixation of CO2 in Assistance of Polymer‐Supported Palladium Catalyst

Abstract: In this work, a functionalized chloromethylated polystyrene supported polymer complex of palladium was designed and synthesized in the three‐step process. The synthesized heterogeneous Pd(DAP‐DEAS‐MERF) catalyst was characterized by Field emission scanning electron microscopy, Energy dispersive analysis of X‐rays, Elemental mapping, Atomic absorption spectroscopy, N2‐BET adsorption‐desorption isotherm, High‐resolution transmission electron microscopy, Thermogravimetric analysis‐Differential thermal analysis, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The In addition to palladium, other elements such as C, N, and O were also present and were examined by EDAX, as shown in Figure 13(iii). 265 In 2021, Zhiani et al reported the synthesis of zinc oxide nanoparticles grafted onto DFNS to utilize CO 2 to synthesize quinazoline-2,4-diones. The synthesized catalyst was characterized by SEM and TEM, which showed spherical morphology.…”
Section: Heterogeneous Catalytic Approach For the Synthesis Of Quinaz...mentioning
confidence: 99%
See 2 more Smart Citations
“…The In addition to palladium, other elements such as C, N, and O were also present and were examined by EDAX, as shown in Figure 13(iii). 265 In 2021, Zhiani et al reported the synthesis of zinc oxide nanoparticles grafted onto DFNS to utilize CO 2 to synthesize quinazoline-2,4-diones. The synthesized catalyst was characterized by SEM and TEM, which showed spherical morphology.…”
Section: Heterogeneous Catalytic Approach For the Synthesis Of Quinaz...mentioning
confidence: 99%
“…The catalyst had a rough surface determined by FE-SEM as shown in Figure (ii). In addition to palladium, other elements such as C, N, and O were also present and were examined by EDAX, as shown in Figure (iii) …”
Section: Current Status Of Co2 Fixation To Form Quinazolinementioning
confidence: 99%
See 1 more Smart Citation